2005
DOI: 10.1111/j.1346-8138.2005.tb00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis Cutis Dyschromica: A Case Treated with Acitretin

Abstract: We report a case of amyloidosis cutis dyschromica with diffuse postinflammatory-type hypo- and hyperpigmentation all over the body. The diagnosis was confirmed with routine light microscopic and immunohistochemical staining methods. The patient was treated with acitretin with a good response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
1
34
0
1
Order By: Relevance
“…However, only wide-spectrum cytokeratin antibodies or high molecular weight cytokeratin antibodies were used in these reports. Wide-spectrum anti-cytokeratin antibodies were positive in two of the three cases [12,16], and high molecular weight cytokeratin was positive in another patient [5]. In our series, 100% (6/6) of the cases showed immunohistochemical positivity for CK34βE12 and CK5/6 and negative or faint positive staining for pan-cytokeratin AE1/AE3.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, only wide-spectrum cytokeratin antibodies or high molecular weight cytokeratin antibodies were used in these reports. Wide-spectrum anti-cytokeratin antibodies were positive in two of the three cases [12,16], and high molecular weight cytokeratin was positive in another patient [5]. In our series, 100% (6/6) of the cases showed immunohistochemical positivity for CK34βE12 and CK5/6 and negative or faint positive staining for pan-cytokeratin AE1/AE3.…”
Section: Discussionsupporting
confidence: 47%
“…The damage may then result in keratinocyte deposition and degenerate to amyloid at the dermo-epidermal junction [18]. Only 3 reports in the literature reported the keratin composition of the amyloid in ACD [5,12,16]. However, only wide-spectrum cytokeratin antibodies or high molecular weight cytokeratin antibodies were used in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Acitretin was given and seems to be effective because it may act by minimizing keratinization defect that causes keratin degeneration to amyloid as proposed by some to be the pathogenesis of this disorder. 10 Qiao et al in his series has convincingly shown 100% positivity to immunohistochemical staining for keratin, CK34 E12 and CK5/6, that the amyloid is thought to be of epidermal origin. 6 This finding seems to agree with the work of Moriwaki et al 9 that points at a disturbance of keratinocyte repairs after irradiation with ultraviolet.…”
Section: Discussionmentioning
confidence: 94%
“…topical corticosteroids, tretinoin, cryotherapy and carbon dioxide laser have varying effects. Systemic acitretin have been applied and suggest a good response [17]. …”
Section: Discussionmentioning
confidence: 99%